International Conference on Psychology, Education and Mental Health. Education Innovation and Mental Health in Industrial Era 4.0 - Maputra, Yantri (De Gruyter, 2021)
Indonesian Psychology Research that primarily focuses on education and mental health, is trying to take a tremendous share to reveal the consequences of industrial development which influence psychological, educational, and mental health factors of humans. The 1st International Conference on Psychology, Education, and Mental Health has proven its commitment to arise the spirit of scientist which provide insight, innovation, and creativity to resolve the problems in psychological field which occurred in this industrial development era. Hundreds of scientists, professionals, and students has gathered to discuss, analyze, and express their opinions about current issues today. We are proud because we can bridge their efforts in a prestigious scientific gathering in Indonesia The 1st ICoPEM 2019. We are enthusiastic to welcome you at the 1st International Conference on Psychology, Education, and Mental Health 2019 to be held in Padang, West Sumatera, Indonesia, 8-10 September 2019. Aims and Scope This event will bring together psychology experts, psychology researcher, psychology lecturer, and students worldwide. We expect it to be a great opportunity and an inspiring occasion for research development learning, especially to disseminating of new findings in psychology and to bridge the networking of psychology professional, psychology researcher and psychology educator. Scopes: Education Techniques of teaching and learning Literacy and skill development Digital technology on education Creativity and entrepreneurship education Innovation and value on education Health Profession Education. Psychology and Counseling Adult and Continuing Education Educational Theory Education Policy Civic Education and Leadership Specia